Sensitization of tumour cells to lysis by virus-specific CTL using antibody-targeted MHC class I/peptide complexes. - Ogg, G; Dunbar, P; Cerundolo, V; McMichael, A; Lemoine, N; Savage, P (2000)
A number of cell surface molecules with specificity to tumour cells have been identified and monoclonal antibodies (mAb) to some of these antigens have been used for targeting tumour cells in vivo. We have sought to link the powerful effector mechanisms of cytotoxic T-cells with the specificity of mAb, by targeting recombinant HLA class I molecules to tumour cells using an antibody delivery system. Soluble recombinant MHC class I/peptide complexes including HLA-A2.1 refolded around an immunodominant peptide from the HIV gag protein (HLA-A2/gag) were synthesized, and the stability of these complexes at 37 degrees C was confirmed by enzyme-linked immunosorbent assay using a conformation-specific antibody. MHC class I-negative lymphoma cells (Daudi) were labelled with a biotinylated mAb specific for a cell surface protein (anti-CD20) then linked to soluble biotinylated HLA-A2/gag complexes using an avidin bridge. Flow cytometry revealed strong labelling of lymphoma cells with HLA-A2/gag complexes (80-fold increase in mean channel fluorescence). CTL specific for HLA-A2/gag efficiently lysed complex-targeted cells, while control CTL (specific for an HLA-A2.1-restricted epitope of melan-A) did not. Similarly, SK-mel-29 melanoma cells were also efficiently lysed by HLA-A2/gag-specific CTL when HLA-A2/gag complexes were linked to their surface via the HMW-MAA specific anti-melanoma antibody 225.28s. With further consideration to the in vivo stability of the MHC class I/peptide complexes, this system could prove a new strategy for the immunological therapy of cancer.